Self-assembling dipeptide antibacterial nanostructures with membrane disrupting activity - Lee Schnaider (Nature Portfolio, 2017)
Peptide-based supramolecular assemblies are a promising class of nanomaterials with important biomedical applications, but their antibacterial properties can be overlooked. Here the authors show the antibacterial activity of self-assembled diphenylalanine, which emerges as the minimal model for antibacterial supramolecular polymers.